The radical right in britain : - Sykes, Alan (Palgrave Macmillan, 2005)
In many and varied forms, the Radical Right has been a hyper-nationalist thorn in the side of Britain's liberal political system for over 100 years. This survey examines its troublesome history, and its critique of British society, from its origins in Edwardian fears of imperial disintegration and racial decay to the current resurgence of the newly modernized British National Party.